College mathematics for business, economics, life sciences and social sciences - Barnett, Raymond A.; $aZiegler, Michael R.; Byleen, Karl E. (Always learning., 2015)
For courses covering finite mathematics and/or calculus for students in business, economics, social sciences, or life sciences. Barnett/Ziegler/Byleen is designed to help students help themselves succeed in the course. This text offers more built-in guidance than any other on the market-with special emphasis on prerequisites skills-and a host of student-friendly features to help students catch up or learn on their own. The content is organized into three parts: (1) A Library of Elementary Functions (Chapters 1-2), (2) Finite Mathematics (Chapters 3-9), and (3) Calculus (Chapters 10-15).